Avaliação de rendimento de frango caipira criados em aviários móveis com diferentes tipos de cobertura - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The objective of this work was to evaluate the carcass and commercial cuts yield in free range chickens raised in mobile poultry houses with different types of cover. The experiment was carried out from August 15 to October 03, 2017. Thirty free-range chickens, 21 days old and with an initial average weight of 306 grams were used. The treatments had three different types of cover, where: 1) cardboard coated with long life packaging (Tetra Pak®), with metallic side facing outwards; 2) roof covering with fibro asbestos tile; and 3) straw roof covering. Carcass, chest, legs (thighs + drumsticks), wings, back, head + neck, feet yields were determined. Relative humidity and temperature and humidity index were collected by means of a HOBO® Pro v2 Datalogger inserted inside the poultry at a height of 0.70 m from the ground. There was a significant interaction (P> 0.05) between the live weight, carcass, breast, leg, wings and back factors of the birds raised in the straw-covered aviary. Mean internal temperature of the poultry house, Relative Humidity for bird comfort and Temperature and Humidity Index were above the bird comfort range. The animals raised in straw-covered mobile poultry houses showed significantly higher carcass and breast yield than the other treatments. Given the variables proposed in this study, it was concluded that the birds raised in the straw-covered aviary had better carcass yield and cuts than the tetra-pak and asbestos-covered poultry, providing the birds a better welfare and consequently raising the carcass production.
Keywords: Desempenho; Avicultura alternativa; Ambiência; CNPQ:: CIÊNCIAS AGRÁRIAS